Is It Possible to Protract the Maxilla by Surgically Assisted Rapid Maxillary Expansion and Intermaxillary Class III Elastics? - Emir Bahman Şahbaz; Emre Cesur; Ayşe Tuba Altuğ; Kutay Can Ergül; Hakan Alpay Karasu; Ufuk Toygar Memikoğlu (Galenos Yayinevi, 2019)
Objective:The purpose of the present study was to evaluate skeletal and soft tissue changes with surgically assisted rapid maxillary expansion (SARME) and intermaxillary Class III elastics.Methods:A total of 15 patients (mean age: 19.58 years) were included in the study. Each patient underwent SARME with the use of Class III elastics (500 g) applied through miniscrews to stimulate maxillary advancement. Lateral cephalograms and posteroanterior radiographs obtained before treatment (T1), after SARME and elastic use (T2), and after treatment (T3) were analyzed to determine the changes in each phase of treatment. Planimeter was used to evaluate facial soft tissue changes. Wilcoxon signed-rank test was used to evaluate the changes that occur during treatment.Results:SARME provided permanent and efficient maxillary expansion at both skeletal and dental levels (p<0.01). Maxillary skeletal (ANS-Ver and U1i-Ver; p<0.01) and soft tissue (Pr-Ver, Sn-Ver, and ULA-Ver; p<0.01) variables and superior upper labial area (Area 1; p<0.05) increased due to maxillary dental and skeletal changes. Superior lower labial area (Area 3; p<0.05) decreased as a result of slight increase in facial height and changes in maxillary-mandibular incisor relationship at the end of the treatment.Conclusion:The results suggest that the improvement in the facial profiles of the patients is related to the significant increase in the bony and dental support of the upper lip region together with the contribution of the superior lower lip area.